Public health impact and return on investment of Belgium’s pediatric immunization program - Carrico, Justin; Mellott, Claire E.; Talbird, Sandra E.; Bento-Abreu, André; Merckx, Barbara; Vandenhaute, Jessica; Benchabane, Damia; Dauby, Nicolas; Ethgen, Olivier; Lepage, Philippe; Luyten, Jeroen; Raes, Marc; et al. (Frontiers in Public Health, 2023)
Objective: We evaluated the public health impact and return on investment of Belgium’s pediatric immunization program (PIP) from both healthcare-sector and societal perspectives. Methods: We developed a decision-analytic model for 6 vaccines routinely administered in Belgium for children aged 0-10 years: DTaP-IPV-HepB-Hib, DTaP-IPV, MMR, PCV, rotavirus, and meningococcal type C. We used separate decision trees to model each of the 11 vaccine-preventable pathogens. The 2018 birth cohort was followed over its lifetime. The model projected and compared health outcomes and costs with and without immunization (based on vaccine-era and pre–vaccine-era disease incidence estimates, respectively), assuming that observed reductions in disease incidence were fully attributable to vaccination. For the societal perspective, the model included productivity-loss costs associated with immunization and disease in addition to direct medical costs. The model estimated discounted cases averted, disease-related deaths averted, life-years gained, quality-adjusted life-years gained, costs (2020 euros), and an overall benefit-cost ratio. Scenario analyses considered alternate assumptions for key model inputs. Results: Across all 11 pathogens, we estimated that the PIP prevented 226,000 cases of infections and 200 deaths, and losses of 7,000 life-years and 8,000 quality-adjusted life-years over the lifetime of a birth cohort of 118,000 children. The PIP was associated with discounted vaccination costs of €91 million from the healthcare-sector perspective and €122 million from the societal perspective. However, vaccination costs were more than fully offset by disease-related costs averted, with the latter amounting to a discounted €126 million and €390 million from the healthcare-sector and societal perspectives, respectively. As a result, pediatric immunization was associated with overall discounted savings of €35 million and €268 million from the healthcare-sector and societal perspectives, respectively; every €1 invested in childhood immunization resulted in approximately €1.4 in disease-related cost savings to the health system and €3.2 in cost savings from a societal perspective. Estimates of the value of the PIP were most sensitive to changes in input assumptions for disease incidence, productivity losses due to disease-related mortality, and direct medical disease costs. Conclusion: Belgium’s PIP provides large-scale prevention of disease-related morbidity and premature mortality, and is associated with net savings to health system and society.